2023
DOI: 10.1186/s12905-023-02617-4
|View full text |Cite
|
Sign up to set email alerts
|

Mother-daughter communication of sexual and reproductive health (SRH) matters and associated factors among sinhalese adolescent girls aged 14–19 years, in Sri Lanka

D. Mataraarachchi,
Pathirana T.E. A,
Mahesh Buddhika P.K
et al.

Abstract: Introduction School-based and community-based sexuality education has not shown a significant impact on the sexual and reproductive health (SRH) outcomes of Sri Lankan adolescents. Parents, as the primary educators of adolescents, could potentially serve as better sources for providing individualized sexuality education to their children. Objective To assess the sexual and reproductive health (SRH) topics discussed between mothers and daughters, ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Community-based research studies have also demonstrated that mother/daughter interventions that provide vaccination to young girls and self-collection to their mothers are feasible and effective [ 24 ]. Working in mother-daughter dyad collaborations for HPV and cervical cancer also aligns with the cultural norms in low income settings where girls are seen to largely defer to their mothers/mother figures in issues regarding their sexual and reproductive health [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based research studies have also demonstrated that mother/daughter interventions that provide vaccination to young girls and self-collection to their mothers are feasible and effective [ 24 ]. Working in mother-daughter dyad collaborations for HPV and cervical cancer also aligns with the cultural norms in low income settings where girls are seen to largely defer to their mothers/mother figures in issues regarding their sexual and reproductive health [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was based on the views and concerns of its users. Results of a descriptive-cross sectional study that was conducted among the adolescents in the study setting [ 15 ] and findings of a qualitative study carried out among mothers of adolescent girls to explore their views on providing sexual health information to their children [ 12 ] were taken into account during the intervention development.…”
Section: Methodsmentioning
confidence: 99%